A high-density graphite-based composite material and a method for producing the same
Patent Information
- Application Number
- CN202611213990.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
然而,石墨材料自身扩散系数小、石墨粉末的层间结合力弱及固有的结构各向异性阻碍了颗粒的结合及致密化,石墨粉末即使在超过2300℃的温度和数十MPa的压力下也无法完全致密化,限制了其在航空航天等高性能领域的应用
本发明高密度石墨基复合材料的制备方法中,通过在混合鳞片石墨粉末表面预先沉积多层垂直石墨烯作为烧结助剂,多层垂直石墨烯是通过化学气相沉积工艺CVD在石墨基体表面原位生长,可实现石墨烯的均匀分布及大面积覆盖,避免了单层石墨烯及商用石墨烯粉末的易团聚现象,减少了因石墨烯在鳞片石墨粉末基体中分布不均,热压烧结后致密度差且存在大量缺陷的问题。其次垂直石墨烯可以有效填充石墨粉末颗粒间隙,其独特的三维网络结构在烧结过程中更有助于传递压力,促进石墨致密化,同时垂直石墨烯的边缘含有大量活性位点,在热压烧结过程中更容易与石墨粉末形成化学键合,垂直取向可使石墨烯片层与基体粉末形成钉扎结构,有效阻止裂纹扩展。本发明采用纳米-微米双粒径鳞片石墨粉末充分均匀混合,大颗粒提供骨架支撑,小颗粒优先烧结填充孔隙,形成骨架-填充的协同致密化机制,使得孔隙尺寸分布更加均匀,且显著提高了鳞片石墨粉末的松装密度,促进后续烧结致密化。本发明以沉积的石墨烯作为烧结助剂,石墨烯与石墨基体同为碳材料,属于同质助烧,不引入任何杂质元素,保持了材料的高纯度和本征性能。本发明采用一次CVD沉积和一次热压烧结即可完成,CVD沉积采用甲醇作为碳源,原料易得、成本低廉;纯石墨粉在温度压力双重作用下即可达到高度致密,烧结在真空或惰性气体保护下进行,无污染排放,环境友好。本发明工艺简单,成型性好,周期短,具有广泛的工业应用前景。
Smart Images

Figure CN122916672A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of graphite-based composite material preparation technology, specifically relating to a high-density graphite-based composite material and its preparation method. Background Technology
[0002] Graphite-based composite materials are widely used in aerospace, nuclear energy, and electronics fields due to their excellent high-temperature stability, high thermal conductivity, ablation resistance, and good chemical stability. However, the small diffusion coefficient of graphite materials, the weak interlayer bonding force of graphite powder, and the inherent structural anisotropy hinder particle bonding and densification. Even at temperatures exceeding 2300℃ and pressures of tens of MPa, graphite powder cannot be fully densified, limiting its application in high-performance fields such as aerospace.
[0003] Currently, high-density graphite preparation methods include chemical vapor deposition (CVD) and sintering. CVD can produce high-density pyrolytic graphite materials, but its deposition efficiency is slow, the preparation cycle is long, and it exhibits strong anisotropy. Conventional graphite sintering methods suffer from insufficient pressure, making densification difficult. Sintering aids are needed to promote densification. To avoid the influence of heterogeneous materials on the intrinsic properties of graphite materials, there is an urgent need to develop a simple, short-cycle process capable of producing high-density graphite (>2.2 g / cm³). 3 A method for preparing graphite-based composite materials that are isotropic and free from impurities. Summary of the Invention
[0004] To address the problems existing in the prior art, the present invention aims to provide a high-density graphite-based composite material and its preparation method. The present invention has a simple process, short cycle, and the prepared material has high density, excellent mechanical properties, and no impurity elements are introduced.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-density graphite-based composite material includes the following steps: Nanoscale flake graphite powder and microscale flake graphite powder are uniformly mixed to obtain mixed flake graphite powder. The mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder to obtain precursor powder; wherein, the grown graphene is used as a sintering aid in hot pressing sintering. The precursor powder is pre-pressed to obtain a pre-pressed blank; The pre-pressed blank is hot-pressed and sintered; after hot pressing and sintering, it is cooled and then demolded to obtain the high-density graphite-based composite material.
[0006] Preferably, nano-sized flake graphite powder and micro-sized flake graphite powder are uniformly mixed to obtain mixed flake graphite powder, specifically including the following process: Micron-sized flake graphite powder was dissolved in anhydrous ethanol to form a suspension. The ratio of micron-sized flake graphite powder to anhydrous ethanol was 0.5–1 g of micron-sized flake graphite powder per 20 ml of anhydrous ethanol. Then, nano-sized flake graphite powder was added to the suspension and simultaneously ground and mixed. After the nano-sized flake graphite powder was added, the mixture was ball-milled uniformly using a planetary ball mill at a speed of 390–410 r / min for 2–12 h. The mixture was then dried at 60–80 °C for 12–24 h to obtain the mixed flake graphite powder.
[0007] Preferably, the particle size of the nano-sized flake graphite powder is 20-100 nm; the particle size of the micro-sized flake graphite powder is 3-5 μm.
[0008] Preferably, the mass ratio of the micron-sized flake graphite powder to the nano-sized flake graphite powder is 1:1 to 1:1.5.
[0009] Preferably, when the mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder to obtain the precursor powder: Methanol was used as the carbon source, the deposition time was 1–12 h, the deposition temperature was 1140–1200 °C, the heating rate was 5–10 °C / min, and the atmosphere was inert gas or vacuum.
[0010] Preferably, when the mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder to obtain the precursor powder: The amount of flake graphite powder deposited in a single deposition process is 0.5–2 g.
[0011] Preferably, when the precursor powder is pre-pressed, it is pressed at 5-8 MPa and then held at that pressure for 10-20 seconds.
[0012] Preferably, the mass of the pre-pressed blank is 0.2 to 1 g.
[0013] Preferably, when the pre-pressed blank is hot-pressed and sintered, the sintering temperature is 2000-2100℃, the pressure is 5.9-6.1GPa, the heating rate is 50-100℃ / min, the holding time is 15-30min, and the atmosphere is vacuum or inert gas.
[0014] This invention also provides a high-density graphite-based composite material, which is prepared by the method described above, and the density of the high-density graphite-based composite material is 2.196–2.23 g / cm³. 3 Its flexural strength is 64–84 MPa.
[0015] The present invention has the following beneficial effects: In the preparation method of the high-density graphite-based composite material of this invention, multilayer vertical graphene is pre-deposited on the surface of mixed flake graphite powder as a sintering aid. The multilayer vertical graphene is grown in situ on the graphite matrix surface by chemical vapor deposition (CVD), which can achieve uniform distribution and large-area coverage of graphene, avoiding the easy agglomeration phenomenon of single-layer graphene and commercial graphene powder. This reduces the problems of poor density and numerous defects after hot pressing sintering due to uneven distribution of graphene in the flake graphite powder matrix. Secondly, vertical graphene can effectively fill the gaps between graphite powder particles. Its unique three-dimensional network structure is more conducive to pressure transmission during sintering, promoting graphite densification. At the same time, the edges of vertical graphene contain a large number of active sites, which are more likely to form chemical bonds with graphite powder during hot pressing sintering. Vertical orientation can make the graphene sheets and the matrix powder form a pinning structure, effectively preventing crack propagation. This invention utilizes a thorough and uniform mixing of nano- and micron-sized flake graphite powders. Larger particles provide skeletal support, while smaller particles preferentially sinter to fill pores, forming a synergistic densification mechanism between the skeletal structure and the filling material. This results in a more uniform pore size distribution and significantly improves the loose packing density of the flake graphite powder, promoting subsequent sintering densification. Deposited graphene is used as a sintering aid. Since graphene and the graphite matrix are both carbon materials, this homogeneous sintering aid introduces no impurities, maintaining the material's high purity and intrinsic properties. This invention can be completed in a single CVD deposition and hot-pressing sintering process. The CVD deposition uses methanol as the carbon source, making the raw materials readily available and inexpensive. Pure graphite powder achieves high densification under the combined effects of temperature and pressure. Sintering is carried out under vacuum or inert gas protection, resulting in zero pollution emissions and environmental friendliness. This invention features a simple process, good formability, and short cycle time, making it promising for broad industrial applications.
[0016] Furthermore, by controlling the particle size distribution of graphite powder and the sintering process, the anisotropy and properties of the material can be adjusted to make it more balanced. A high proportion of coarse powder leads to obvious layered orientation and strong anisotropy, while a high proportion of fine powder results in more interfaces and a decrease in overall performance. Moreover, the density is relatively high when the ratio of coarse powder to fine powder is between 1:1 and 1:1.5. When the difference between the ratio of coarse powder and fine powder is too large, the loose density of the mixed powder is low, and the overall density of the obtained graphite-based composite material is reduced. Attached Figure Description
[0017] Figure 1This is a physical image of the high-density graphite-based composite material in Example 1 of the present invention.
[0018] Figure 2 The images shown are scanning electron microscope (SEM) images of graphite powder and graphene after 2 hours of graphene deposition in Example 2 of this invention.
[0019] Figure 3 The images shown are scanning electron microscope (SEM) images of graphite powder and graphene after 4 hours of graphene deposition in Example 1 of this invention.
[0020] Figure 4 The images shown are scanning electron microscope (SEM) images of graphite powder and graphene after 8 hours of graphene deposition in Example 4 of this invention.
[0021] Figure 5 The images shown are scanning electron microscope (SEM) images of graphite powder and graphene after 12 hours of graphene deposition in Comparative Example 1 of this invention.
[0022] Figure 6 This is a scanning electron microscope image of the graphite-based composite material sintered from pure graphite powder in Comparative Example 2 of this invention.
[0023] Figure 7 This is a scanning electron microscope image of a high-density graphite-based composite material with graphene deposited for 2 hours in Example 2 of this invention.
[0024] Figure 8 This is a scanning electron microscope image of the high-density graphite-based composite material with graphene deposited for 4 hours in Example 1 of the present invention.
[0025] Figure 9 This is a scanning electron microscope image of the high-density graphite-based composite material with graphene deposited for 4 hours in Example 3 of the present invention.
[0026] Figure 10 This is a scanning electron microscope image of a high-density graphite-based composite material with graphene deposited for 8 hours in Example 4 of this invention.
[0027] Figure 11 This is a scanning electron microscope image of the fracture surface of the non-uniformly mixed high-density graphite-based composite material in Comparative Example 4 of the present invention. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] To address the challenge of achieving high density in conventional graphite materials, this invention proposes a high-density graphite-based composite material and its preparation method. The method involves thoroughly and uniformly mixing nano- to micron-sized flake graphite powder, then growing graphene on the flake graphite surface using CVD to obtain a mixed graphite powder. This mixed graphite powder is pre-pressed into a sintering mold and finally hot-pressed at 6±0.1 GPa pressure and 2000–2100℃ for 15–30 min. Under the combined effects of temperature and pressure, plastic flow and volume diffusion occur within the material. Carbon atom diffusion connects the discrete graphite particles and graphene sheets, promoting densification and eliminating internal porosity. The resulting hot-pressed composite material achieves a density of up to 2.225 g / cm³. 3 High-density graphite-based composite materials.
[0030] The method for preparing the high-density graphite-based composite material of the present invention includes the following steps: (1) Dissolve 3-5μm flake graphite powder in anhydrous ethanol and ultrasonically disperse for 30 min to prepare a suspension; then add 20-100nm flake graphite powder to the suspension and grind and mix it while adding the 20-100nm flake graphite powder. The mass ratio of the two flake graphite powders is 1:1 to 1:1.5: coarse powder (i.e., 3-5μm flake graphite powder): fine powder (i.e., 20-100nm flake graphite powder). The mixture of coarse powder and fine powder is loaded into a planetary ball mill for ball milling and mixing. The ball milling speed is 400±10r / min and the ball milling time is 2 to 12h. After ball milling, dry it in an oven at 60 to 80℃ for 12 to 24h to obtain mixed flake graphite powder. Use the mixed flake graphite powder as the matrix raw material for chemical vapor deposition.
[0031] (2) The mixed flake graphite powder is placed in a chemical vapor deposition furnace, using methanol (CH3OH) as the carbon source, and heated to 1140–1200℃ at a heating rate of 5–10℃ / min. Graphene is deposited on the surface of the graphite flakes by CVD for 1–12 hours to obtain precursor powder. The atmosphere during deposition is inert gas or vacuum, and the amount of flake graphite powder deposited in a single deposition is 0.5–2 g. This step enables the growth of multilayer vertical graphene on the surface of the flake graphite powder, and the grown graphene serves as a sintering aid in hot pressing sintering.
[0032] (3) Take 0.2-1g of precursor powder and put it into the mold, pre-press it, and put the pre-pressed blank into the sintering mold; wherein, the pressure during pre-pressing is 5-8MPa and the holding time is 10-20s.
[0033] (4) Place the pre-pressed blank from step (3) together with the sintering mold into a hot pressing sintering equipment, and then sinter in a vacuum or inert gas environment; wherein the sintering temperature is 2000~2100℃, the pressure is 6±0.1GPa, the heating rate is 50~100℃ / min, and the holding time is 15~30min. (5) After sintering, the temperature is reduced and the pressure is released. After cooling, the mold is removed to obtain the high-density graphite-based composite material.
[0034] The high-density graphite-based composite material prepared by the above method of the present invention contains nano- and micro-sized flake graphite powder and multilayer vertical graphene, wherein the graphene is grown on the surface of the flake graphite powder and the particle size range of the flake graphite powder is 20 nm to 5 μm.
[0035] Example 1: The preparation method of the high-density graphene / graphite composite material in this embodiment includes the following steps: (1) Mixing: 1g of flake graphite powder with a particle size of 3-5μm is added to 20ml of anhydrous ethanol and ground. Then, an equal mass of flake graphite powder with a particle size of 50-100nm is added. During the addition process, grinding and mixing are carried out. After the flake graphite powder with a particle size of 50-100nm is added, it is loaded into a planetary ball mill for mixing. The ball milling speed is 400r / min and the ball milling time is 4h. After the ball milling is completed, the slurry is taken out and dried in an oven at 70℃ for 12h to obtain mixed flake graphite powder.
[0036] (2) Graphene deposition: Graphene was deposited on the surface of mixed flake graphite powder by chemical vapor deposition (CVD). Methanol was used as the carbon source. 1g of mixed flake graphite powder was placed in the CVD furnace, the heating rate was 7.5℃ / min, the deposition temperature was 1160℃, and the deposition time was 4h. After the deposition was completed, the precursor powder was obtained.
[0037] (3) Loading: Place the precursor powder in a mold with an inner diameter of 8 mm, apply pressure to pre-press it, the pressure is 5 MPa, the holding time is 15 s, and then put the pre-pressed blank obtained after pre-pressing into a sintered graphite mold.
[0038] (4) Sintering: The pre-pressed blank and sintering mold from step (3) are placed into the sintering equipment. The sintering method is hot pressing sintering. The sintering pressure is 6 GPa. After the sintering pressure stabilizes, the temperature is raised to the sintering temperature at a rate of 100℃ / min. The sintering temperature is 2000℃ and the holding time is 15 min. After the holding time is completed, the heating program is turned off and the temperature is lowered and the pressure is released. (5) Discharge: After the equipment cools down and the pressure is released, the mold is removed and the high-density graphite-based composite material is obtained.
[0039] After preparation, the density of the obtained high-density graphite-based composite material was tested.
[0040] Test results show that the density of the graphite-based composite material obtained after hot pressing and sintering is 2.225 g / cm³. 3 Its density reaches the extremely high density level of graphite.
[0041] Example 2 The preparation method of the graphite-based composite material in this embodiment is basically the same as that in Example 1. The specific process parameters and properties that differ from those in Example 1 are shown in Table 1.
[0042] Example 3 The preparation method of the graphite-based composite material in this embodiment is basically the same as that in Example 1. The specific process parameters and properties that differ from those in Example 1 are shown in Table 1.
[0043] Example 4 The preparation method of the graphite-based composite material in this embodiment is basically the same as that in Example 1. The specific process parameters and properties that differ from those in Example 1 are shown in Table 1.
[0044] Comparative Example 1 The preparation method of the graphite-based composite material in this comparative example is similar to that in Example 1. The specific process parameters and properties that differ from those in Example 1 are shown in Table 1.
[0045] Comparative Example 2 The preparation method of the graphite-based composite material in this comparative example is similar to that in Example 1, but graphene was not deposited as a sintering aid. Specific process parameters and properties are shown in Table 1.
[0046] Comparative Example 3 The preparation method of the graphite-based composite material in this comparative example is similar to that in Example 1, but the sintering temperature is slightly lower. For specific process parameters and properties, please refer to Table 1.
[0047] Comparative Example 4 The preparation method of the graphite-based composite material in this comparative example is similar to that in Example 1, but the raw material is simply mixed flake graphite powder without grinding, ball milling or other uniform mixing. For specific process parameters and properties, please refer to Table 1.
[0048] Comparative Example 5 The preparation method of the graphite-based composite material in this comparative example is similar to that in Example 1. The matrix raw material used is pure nano-graphene with a particle size of 20-100 nm. For specific process parameters and properties, please refer to Table 1.
[0049] Table 1 shows the process parameters and performance comparison of the high-density graphite-based composite materials in each embodiment and comparative example: Table 1
[0050] Table 1 shows that in Comparative Example 1, the process and graphene deposition time were 12 hours. The excessively long deposition time resulted in poor material formability and reduced densification. Comparative Example 2, lacking graphene deposition and sintering aids, had insufficient atomic diffusion channels, leading to low densification. The resulting material had a lower density than graphite material deposited for 2-4 hours and exhibited significant surface cracks. Comparative Example 3 had a lower sintering temperature, resulting in insufficient atomic diffusion and difficulty in eliminating porosity. Comparative Example 4 involved simple mixing of flake graphite powder, leading to severe graphite powder agglomeration that prevented the elimination of gaps generated during sintering, resulting in lower material density and susceptibility to breakage. Comparative Example 5 used pure nanoparticles (20-100 nm) of flake graphite powder, which, while highly dense, failed to achieve the highest density.
[0051] from Figures 2-5 It can be seen that vertical graphene grows uniformly over a large area on the surface of the graphite sheets. As the deposition time of graphene increases, Figures 2-3 The deposition time is 2-4 hours, and graphene is grown on the substrate surface. Figure 4 The deposition time was 8 hours, and the substrate surface was gradually covered, and the graphene sheets began to stack. Figure 5 The deposition time was 12 hours, during which the surface graphene had significantly stacked, the sheets thickened, causing defect deposition, making the material difficult to form and significantly reducing its flexural strength. According to... Figures 6-11 SEM images of high-density graphite-based composite materials revealed that... Figure 6 In Comparative Example 1, the sample without graphene deposition had gaps between its particles that could not be eliminated during the subsequent high-temperature sintering process, resulting in significant cracks on the material surface, making it prone to breakage and exhibiting poor mechanical properties. Figure 7 In Example 2, the sample surface after 2 hours of deposition contained many small particles and pores, resulting in a low porosity. Figure 8 In Example 1, the sample surface after 4 hours was smooth, without obvious cracks, and showed a high degree of densification. Figure 9 In Example 3, the sintering temperature reached 2100°C, resulting in higher surface smoothness in some areas. However, the excessively high temperature led to grain coarsening and microcracks, resulting in delamination and cracks, which negatively affected the density. Figure 10 In Example 4, the sample with graphene deposited for 8 hours exhibited significant porosity defects on its surface after hot pressing and sintering. Figures 7-10 The surface is free of large cracks, and graphene promotes densification and improves the flexural strength of graphite-based composite materials. Figure 11 The powder in Comparative Example 3 was not subjected to grinding, ball milling or other processes to ensure that the nano-micro dual-particle-size powders were fully and uniformly mixed. The agglomeration of its flake graphite powder particles resulted in significant porosity and cracks in the sample, and a significant reduction in density and mechanical properties.
[0052] In summary, this invention uses graphene as a sintering aid to deposit graphene on the surface of flake graphite powder, and then prepares a high-density graphite-based composite material through hot pressing sintering. This invention improves the bulk density by distributing flake graphite powder with dual particle sizes, and by depositing graphene on the surface of graphite flakes, it solves the problems of low graphite atomic diffusion rate and difficulty in eliminating porosity, promoting densification and increasing material density, while also enhancing the material's mechanical properties. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without innovative effort should fall within the scope of protection of this invention.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a high-density graphite-based composite material, characterized in that, The process includes the following: Nanoscale flake graphite powder and microscale flake graphite powder are uniformly mixed to obtain mixed flake graphite powder. The mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder to obtain precursor powder; wherein, the grown graphene is used as a sintering aid in hot pressing sintering. The precursor powder is pre-pressed to obtain a pre-pressed blank; The pre-pressed blank is hot-pressed and sintered; after hot pressing and sintering, it is cooled and then demolded to obtain the high-density graphite-based composite material.
2. The method for preparing a high-density graphite-based composite material according to claim 1, characterized in that, Nanoscale flake graphite powder and microscale flake graphite powder are uniformly mixed to obtain mixed flake graphite powder. The specific process includes the following steps: Micron-sized flake graphite powder was dissolved in anhydrous ethanol to form a suspension. The ratio of micron-sized flake graphite powder to anhydrous ethanol was 0.5–1 g of micron-sized flake graphite powder per 20 ml of anhydrous ethanol. Then, nano-sized flake graphite powder was added to the suspension and simultaneously ground and mixed. After the nano-sized flake graphite powder was added, the mixture was ball-milled uniformly using a planetary ball mill at a speed of 390–410 r / min for 2–12 h. The mixture was then dried at 60–80 °C for 12–24 h to obtain the mixed flake graphite powder.
3. The method for preparing a high-density graphite-based composite material according to claim 1, characterized in that, The nanoscale flake graphite powder has a particle size of 20-100 nm; the microscale flake graphite powder has a particle size of 3-5 μm.
4. A method for preparing a high-density graphite-based composite material according to any one of claims 1-3, characterized in that, The mass ratio of micron-sized flake graphite powder to nano-sized flake graphite powder is 1:1 to 1:1.
5.
5. The method for preparing a high-density graphite-based composite material according to claim 1, characterized in that, When the mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder, the precursor powder is obtained as follows: Methanol was used as the carbon source, the deposition time was 1–12 h, the deposition temperature was 1140–1200 °C, the heating rate was 5–10 °C / min, and the atmosphere was inert gas or vacuum.
6. A method for preparing a high-density graphite-based composite material according to claim 1 or 5, characterized in that, When the mixed flake graphite powder is processed by chemical vapor deposition to grow multiple layers of vertical graphene on the surface of the mixed flake graphite powder, the precursor powder is obtained as follows: The amount of flake graphite powder deposited in a single deposition process is 0.5–2 g.
7. The method for preparing a high-density graphite-based composite material according to claim 1, characterized in that, When the precursor powder is pre-pressed, it is pressed at 5-8 MPa and then held at that pressure for 10-20 seconds.
8. A method for preparing a high-density graphite-based composite material according to claim 1 or 7, characterized in that, The mass of the pre-pressed blank is 0.2 to 1 g.
9. The method for preparing a high-density graphite-based composite material according to claim 1, characterized in that, When the pre-pressed blank is hot-pressed and sintered, the sintering temperature is 2000-2100℃, the pressure is 5.9-6.1GPa, the heating rate is 50-100℃ / min, the holding time is 15-30min, and the atmosphere is vacuum or inert gas.
10. A high-density graphite-based composite material, characterized in that, The high-density graphite-based composite material is prepared by the preparation method according to any one of claims 1-9, and the density of the high-density graphite-based composite material is 2.196-2.23 g / cm³. 3 Its flexural strength is 64–84 MPa.